Ethnic groups difference in discriminatory attitude towards HIV/AIDS patients among medical students: a cross-sectional study - Chew, Boon How; Cheong, Ai Theng (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2014)
Medical students are future doctors who are trained to treat all kinds of diseases including people living with HIV/AIDS (PLWHA) without prejudice. Teaching basic scientific knowledge and technical skills is no longer adequate for today’s medical students. There is also a need for them to be provided with high personal and professional values. This study examined stigmatizing attitude towards people living with HIV/AIDS (PLWHA) among the medical students in a public medical school. The participants were stratified to preclinical-year (year 1 and year 2) and clinical-year (year 3 and year 4) medical students. Simple random sampling was carried out to select 170 participants from each category of students. Self-administered questionnaires captured socio-demographic data, HIV/AIDS knowledge and stigmatisation attitudes towards PLWHA. Multiple linear regressions was used to assess the relationship between ethnic groups and stigmatization attitude. Three hundred and forty participants were recruited. Malay medical students who did not have previous encounter with PLWHA were associated with stigmatizing attitude towards HIV/AIDS patients, whereas clinical-year medical students who had no clinical encounter with PLWHA were more likely to feel uncomfortable with PLWHA. Malay ethnicity and medical students in clinical years who had not encounter a PLWHA were more likely to have stigmatizing attitude towards PLWHA.